2011 IEEE 17th International Symposium on High Performance Computer Architecture 2011
DOI: 10.1109/hpca.2011.5749756
|View full text |Cite
|
Sign up to set email alerts
|

Hardware/software techniques for DRAM thermal management

Abstract: The performance of the main memory is an important factor on overall system performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…We show 2 Figure 22 in [12] and Figure 3 in [43] show that the maximum temperature of DRAM chips at the highest CPU utilization is 60-65 • C. While some prior works claim a maximum DRAM temperature over 80 • C [76], each DIMM in their system dissipates 15W of power. This is very aggressive nowadays -modern DIMMs typically dissipate around 2-6W (see Figure 8 of [17], 2-rank configuration same as the DIMM configuration of [76] this in Figure 5, which plots the temperature for a 24-hour period (left) and also zooms in on a 2-hour period (right).…”
Section: Temperature Dependence: Hot Cells Are Leakiermentioning
confidence: 79%
See 2 more Smart Citations
“…We show 2 Figure 22 in [12] and Figure 3 in [43] show that the maximum temperature of DRAM chips at the highest CPU utilization is 60-65 • C. While some prior works claim a maximum DRAM temperature over 80 • C [76], each DIMM in their system dissipates 15W of power. This is very aggressive nowadays -modern DIMMs typically dissipate around 2-6W (see Figure 8 of [17], 2-rank configuration same as the DIMM configuration of [76] this in Figure 5, which plots the temperature for a 24-hour period (left) and also zooms in on a 2-hour period (right).…”
Section: Temperature Dependence: Hot Cells Are Leakiermentioning
confidence: 79%
“…• C [11,12,43]. 2 We measured the DRAM ambient temperature in a server cluster running a memory-intensive benchmark, and found that the temperature never exceeds 34…”
Section: Temperature Dependence: Hot Cells Are Leakiermentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies try to reduce temperature of 2D DRAM (DIMMs: Dual In-line Memory Modules) [10,11]. In [10], DRAM memory system is controlled by dynamic thermal management (core gating and dynamic voltage and frequency scaling).…”
Section: Related Workmentioning
confidence: 99%
“…In [10], DRAM memory system is controlled by dynamic thermal management (core gating and dynamic voltage and frequency scaling). In [11], DRAM thermal management is carried out by DRAM-aware techniques (e.g., a new cache line replacement policy, new write buffer design, and page allocation techniques, etc.). However, the above mentioned techniques are geared toward the conventional 2D DRAM systems with DIMMs.…”
Section: Related Workmentioning
confidence: 99%